Enzymatic Interesterification of Cold-Pressed Maqui (Aristotelia chilensis (Mol.) Stuntz) Seed Oil and Belly Oil from Rainbow Trout (Oncorhynchus mykiss) Through Supercritical CO2 - Francisca Reinoso; Alicia Rodríguez; Camila Sánchez; Benjamín Claria; Nalda Romero; Alejandra Espinosa; María Elsa Pando; Rodrigo Valenzuela; Dayana Apaza; Gretel Dovale-Rosabal; Santiago P. Aubourg (Marine Drugs)
A new antioxidant lipid (AL) was synthesized from rainbow trout (Oncorhynchus mykiss) belly oil and cold-pressed maqui (CPM) (Aristotelia chilensis (Mol.) Stuntz) seed oil via enzymatic interesterification using Thermomyces lanuginosus in supercritical CO2 medium. A Box–Behnken design with 15 experiments was employed, with the independent variables being the following: belly oil/CPM oil ratio (10/90, 50/50, and 90/10, w/w), supercritical CO2 temperature (40.0, 50.0, and 60.0 °C), and supercritical CO2 pressure (100.0, 200.0, and 300.0 bar) for enzymatic interesterification. A multiple optimization was conducted based on the response variables yield and eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and tocopherol contents. The optimized conditions for the AL synthesis were: 81.4/18.6 (w/w), 40.0 °C and 299.99 bar, respectively. The corresponding responses variables were: 77.10% for yield, 5.12 and 4.95 g·100 g−1 total fatty acids for EPA and DHA, respectively, and 217.96, 4.28, 3.48, 64.48, and 6.39 mg·kg−1 oil for α-tocopherol, α-tocotrienol, β-tocopherol, γ-tocopherol, and δ-tocopherol, respectively. A novel AL was successfully synthesized starting from two abundant natural resources commonly considered as by-products during industrial processing. In agreement with the high EPA, DHA, and tocopherol presence, this AL can be recommended to be employed in nutritional and therapeutic supplements, according to its health benefits, particularly concerning antioxidant and anti-inflammatory properties.